Síntese e otimização de um sistema energético para um edifício do setor residencial em João Pessoa-PB - Melo, Filipi Maciel de (2017)
The residential sector is a consumer of both electricity and thermal energy (cold and heat). These demands can be met in a conventional way, consuming electricity directly from the grid, or in an unusual way, through the simultaneous production of two or more utilities (cogeneration). An optimization study should be carried out whenever there is a need to ensure the economic viability of a power supply and conversion system. The optimization includes not only the system configuration (equipment to install) but also the operational strategy (how each equipment operates, throughout the year). For this study, the economic, technical and legal aspects were considered, in order to minimize the annual costs with the energy supply of this building. The energy demands of this building were calculated by Energy Plus software, and are 83, 171 and 242 MWh / year for heat (hot water), electricity and cooling, respectively. The optimization study was performed using mixed integer linear programming with Lingo software, in a building located in the city of João Pessoa, latitude -7.11 ° and longitude -34.86 °. The building has 20 floors with two apartments of 92 m2 on each floor. The optimum configuration of the system was traditional: electricity purchased from the electricity grid directly addressed the demand for electricity, and by means of an electric boiler and mechanical chiller, to the demands of heat and cooling, respectively. This result was obtained due to geographic location (low heat demand, making it impossible to use cogeneration), and due to the economic scenario considered, especially the high price of the absorption machine, making trigeration impossible. Sensitivity analysis was performed by varying the price of natural gas, electric energy, demand, the amortization factor and the relationship between the price of electricity and natural gas. The only variation that resulted in cogeneration was the increase of the price difference between electricity and natural gas.